Instrument for evaluating care given by undergraduate nursing students to people with wounds - Roberta Kaliny de Souza Costa; Gilson de Vasconcelos Torres; Marina de Góes Salvetti; Isabelle Campos de Azevedo; Maria Antônia Teixeira da Costa
OBJECTIVE The aim of this study was to present the process of construction and validation of an instrument for evaluating the care provided to people with wounds, to be used with undergraduate nursing students. METHOD Methodological study, with quantitative approach, using the Delphi technique in two rounds, the first with 30 judges and the second with 18. The analysis was made with Kappa coefficient ≥0.80, and content validity index greater than >0.80, also using the Wilcoxon test for comparison of the indices between the rounds. RESULTS It was found that of the 20 categories of the instrument, 18 presented better scores in the second Delphi round. Scores were greater in the second round in seven of the ten evaluation categories. CONCLUSION Based on the evaluation by the judges, a version of the instrument was defined with adequate indices of agreement and validity, which will be able to help in evaluating care of people with cutaneous injury given by undergraduate nursing students.